A glimpse on influences of feed additives in aquaculture. Issue 1 (23rd May 2022) - Marimuthu, Vignesh; Shanmugam, Sureshkumar; Sarawagi, Anurag Deendayal; Kumar, Abhay; Kim, In Ho; Balasubramanian, Balamuralikrishnan
Abstract: Aquaculture is one of the most developing sectors worldwide, and it contributes to enhancing the global production. The application of natural feed additives is an external source of aquaculture production due to the ban on antibiotics as a growth promotor as well as their harmful effects on the host, and cost‐effectiveness. Even consumer concerns those antibiotics can cause the water quality and growth instead of growth promoters of natural feed additives to improve the aquaculture production. The role of feed additives is to control the pathogenic microbes, enhance their growth, immune stimulation, and ensure water quality. For these reasons, several types of dietary feed additives are used in the livestock sector, such as essential oil, essential fatty acid, probiotics, prebiotics, symbiotic, and exogenous enzymes, but here, the feed additives of probiotics' most relevant applications in the aquaculture field in terms of modes of action such as strengthening the immune response, competition of binding sites, production of antipathogenic substances, and growth performance competition for nutrition are described. These additives are considered to be useful for their specific medicinal properties and eco‐friendly metabolism in the digestive system. This review describes the role of various feed additives and their relevance to aquaculture production quality. Abstract : Schematic diagram of natural feed additives in the aqua sector.